Femmes et conflits dans l’imaginaire historié de la Rome des Valois - Pierre Pretou (E-Spania)
The reception and appropriation of Roman history under the Valois through copies and translations of luxurious manuscripts owned by these kings, their relatives and great officers, connect the medieval imaginary of antiquity to this dynasty. French political iconography of the 14th and 15th centuries combines the governance of the City of Rome with the origins of the kingdom since the translation of Ab Urbe Condita of Tite-Live by Pierre Bersuire, the copies of Jean Mansel's Fleurs des histoires, the translations of De Civitate Dei by Raoul de Presles and the vernacular translation of the writings of Valère Maxime by Simon de Hesdin and Nicolas de Gonesse. By thousands, these miniatures on a universe of men and cities, order and disorder, peace and revenge, concord and discord, identify the public space, the speech, the just power, the contestation, the tyranny, the circulation pacificator of the law, but rarely give way to women, except to associate them with bloody scenes. The serial analysis of the narrow corpus of female representation shows that the appropriation of the image of Roman history gives a singular place to the genre in the representation of conflicts and their resolution in urban areas. The painted women who emerge from Roman stories of the late Middle Ages French escort a world of ancient men experiencing the soothing role of law. Can we conclude for these rare women who accompany scenes of conflict and peace that the painter gives them a historical role as mediators and reinterprets the actions of Roman women? Does he reconsider the construction of public order at the end of the French Middle Ages or is it first of all the historized formulation of a political theory of marriage?